Comparative analysis of storage techniques for a grid with renewable energy sources - Reddy Salkuti, Surender; Mook Jung, Chan (International Journal of Engineering and Technology, 2018)
This paper presents the comparative analysis of different energy storage techniques used in the utility grid connected with the renewable energy sources (RESs). Energy storage is required to match the demand and supply of energy. However, with the integration of RESs to the grid increases the mismatch between the supply and demand due to the intermittence of RESs. In this paper, it is shown that the energy stor-age systems provide a better solution to the integration of different RESs to the existing grid. The energy storage systems are the key com-ponents for replacing the conventional fossil fuel plants with RESs. It is hard to evaluate the different types of energy storage techniques between themselves due to the fact that each technology could be used in a different way and are more like compliments. Further, research needs to be done on storage techniques to continue to increase the benefits while reducing the associated costs. The energy storage tech-niques show great potential to help the RESs and smart grid to meet the worldâ€™s growing energy demand. This paper has presented the comparative analysis of various energy storage systems in terms of their design, cost, geographical location, advantages and disadvantages.Â Â
Keywords: Renewable Energy Sources; Energy Storage; Smart Grid; Flywheel; Battery; Microgrid; Supercapacitors.